Antibacterial Activity of Legundi (Vitex trifolia L.) Fruit Extract Against Lactobacillus gasseri ATCC 19992: Study In Vitro - Cindykia, Assyifa; Lubis, Humairah Medina Liza (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Lactobacillus species are the most frequent bacterial colonies in the human microbiome that can be found in the gastrointestinal tract, urinary tract, and vaginal microbiota. Lactobacillus gasseri is an important constituent of the female urogenital tract. if there is excessive proliferation of Lactobacillus, there will be changes in the homeostasis of the human microbiome. Homeostasis of the human microbiome can undermine the symbiotic relationship between host and microorganisms, induce physiological changes in the individual, and lead to the development of diseases such as to the development of diseases such as cancer. Legundi fruit extract was found to be cytotoxic against several lines of cancer cells and has antimicrobial activity. This research aims to determine the diameter of antibacterial inhibition of Legundi fruit extract, and determine the minimum inhibition concentration (MIC), minimum kill concentration (MKC) against Lactobacillus gasseri. This research used solid and liquid dilution and diffusion methods with concentrations of 10%, 20%, 25%, 50%, 75%, 100%, positive and negative controls. Extract of Legundi fruit can’t inhibit bacterial growth at concentrations of 10% and 20%. The longest diameter was in the positive control with streptomycin. The higher the concentration of Legundi fruit ethanol extract given, the higher the inhibition ability.